2009
DOI: 10.1002/smi.1263
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and depression: the direct and moderating effects of informal social support and coping

Abstract: This article investigated the relationship between job stressors and employee mental health (depression). It also examined the direct and moderating effects of informal social support (objective and subjective) and coping (active coping, overeating and drinking, passivity, and distancing) on the relationships. Survey data were collected from 843 employees in eight types of domestic‐ and foreign‐invested enterprises in China. Hierarchical regression analyses revealed that increased exposure to job stressors was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 42 publications
4
44
1
4
Order By: Relevance
“…However, a few other studies have investigated the buffering effect of other related concepts on the association between psychosocial working conditions and mental health. Several studies have shown that internal resources such as sense of coherence or coping mechanisms buffer the mental health effects of psychosocial work stressors (26)(27)(28)(29)(30). These studies are in conflict with our results, Table 3a.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, a few other studies have investigated the buffering effect of other related concepts on the association between psychosocial working conditions and mental health. Several studies have shown that internal resources such as sense of coherence or coping mechanisms buffer the mental health effects of psychosocial work stressors (26)(27)(28)(29)(30). These studies are in conflict with our results, Table 3a.…”
Section: Discussioncontrasting
confidence: 99%
“…There are some studies using related concepts, such as locus of control or sense of coherence, which suggest moderating effects (26)(27)(28)(29)(30). However, these studies are mainly based on cross-sectional designs with rather small sample sizes.…”
Section: Do Resources Buffer the Effect Of Work Stress On Depressive mentioning
confidence: 99%
“…Igualmente, los estudios realizados en el ámbito internacional han contemplado un panorama especialmente amplio de situaciones. En este sentido, se ha estudiado la relación entre apoyo social y depresión en personas con estrés laboral (Chen, Siu, Lu, Cooper y Philips, 2009); estrés provocado por la amenaza terrorista (Sahar, Gohen, Grogan, Braile y Henrich 2009); la aculturación (Ayers, Hofstetter, Usita, Irvin, Kang y Hovell, 2009); la muerte de un ser querido (Burke y Neimeyer, 2010); o el trauma psicológico (Schumn, Briggs y Hobfoll, 2006). También se ha estudiado el apoyo social, relacionado con variables de personalidad como el perfeccionismo (Shery, Law, Hewitt, Flett y Besser, 2008), el optimismo (Piko, Luszczynska y Fitzpatrick, 2012), o con los más dispares problemas de salud, como infección por sida (Vyavaharkar, Moneyham, Corwin, Saunders, Annang y Tavakoli, 2010); la esclerosis múltiple (Vargas y Arnett, 2010); o procesos oncológicos (Robles, Morales, Jiménez y Morales, 2009).…”
Section: Introductionunclassified
“…Repeating the procedure resulted in receiving consent from only two organizations. Due to concerns about the time constraints and difficulties in recruiting a sufficient number of participants, respondents were selected from 12 manufacturing companies situated in the East (Pahang and Terengganu) and West Coast (Selangor, Johor, Malacca, Negeri Sembilan and Kedah) of Peninsula Malaysia by approaching the top management team members (Chen et al 2009), managers or employees with whom the researcher had professional connections or personal contacts (Lu, Gilmour, Kao & Huang 2006). Furthermore, using purposive and professional connection strategies are justified because the random approach led to a very low response rate from Malaysian organizations that had been involved in previous studies (Idris, Dollard & Winefield 2010).…”
Section: Methodsmentioning
confidence: 99%